A novel solar-geothermal trigeneration system integrating water desalination: Design, dynamic simulation and economic assessment. (15th November 2016) - Calise, Francesco; Dentice d'Accadia, Massimo; Macaluso, Adriano; Vanoli, Laura; Piacentino, Antonio
Abstract: In this paper, an innovative solar-geothermal polygeneration system is investigated. The system supplies a small community with electricity, desalinated water and space heating and cooling through a district network. The hybrid multi-purpose plant, based on an Organic Rankine Cycle (ORC) supplied by medium-enthalpy geothermal energy and by solar energy; this latter is provided by Parabolic Trough Collectors (PTC). The geothermal brine is first used to drive the ORC loop, then to provide space heating at around 85÷90 °C (in the winter), or cooling (in the summer, by means of a single-effect absorption chiller). Finally, the geothermal brine drives a Multi-Effect Distillation (MED) system, where seawater is converted into freshwater. For such a system, a dynamic simulation model was developed in TRNSYS environment. In particular, the ORC model, developed in Engineering Equation Solver (EES), was based on zero-dimensional energy and mass balances and includes specific algorithms to evaluate the off-design performance. Similarly, a novel model of the MED unit was developed in EES. Suitable control strategies were implemented for the optimal management of system. The energy and economic performance of the system under analysis was investigated, using different time bases (day, week, month, year). Finally, a sensitivity analysis was performed to determine the set of system, design/control parameters able to minimize the simple payback period. The results showed that the novel system is highly flexible and efficient. On the other hand, a significant capital cost must be taken into account, so that the system is economically profitable only when the majority of the energy available for heating and cooling purposes is actually used. Highlights: Dynamic simulation and thermoeconomic analyses of renewable system are presented. The system is powered by geothermal source and by a PTC solar field. The system includes an Organic Rankine Cycle. The system produces electric, thermal and cooling energy and desalinated water. Pay back period of about 4.5 year is obtained.